Progress on modified calcium oxide derived waste-shell catalysts for biodiesel production - Ooi, Hui Khim; Koh, Xin Ning; Ong, Hwai Chyuan; Lee, Hwei Voon; Mohd Sufri Mastuli; Yap, Taufiq Yun Hin; Fahad A. Alharthi; Abdulaziz Ali Alghamdi; Nurul Asikin Mijan (Molecular Diversity Preservation International (MDPI), 2021)
The dwindling of global petroleum deposits and worsening environmental issues have triggered researchers to find an alternative energy such as biodiesel. Biodiesel can be produced via transesterification of vegetable oil or animal fat with alcohol in the presence of a catalyst. A heterogeneous catalyst at an economical price has been studied widely for biodiesel production. It was noted that various types of natural waste shell are a potential calcium resource for generation of bio-based CaO, with comparable chemical characteristics, that greatly enhance the transesterification activity. However, CaO catalyzed transesterification is limited in its stability and studies have shown deterioration of catalytic reactivity when the catalyst is reused for several cycles. For this reason, different approaches are reviewed in the present study, which focuses on modification of waste-shell derived CaO based catalyst with the aim of better transesterification reactivity and high reusability of the catalyst for biodiesel production. The catalyst stability and leaching profile of the modified waste shell derived CaO is discussed. In addition, a critical discussion of the structure, composition of the waste shell, mechanism of CaO catalyzed reaction, recent progress in biodiesel reactor systems and challenges in the industrial sector are also included in this review.